Improving long-term postoperative survival in a porcine cardiac valve surgery model utilizing cardiopulmonary bypass via left thoracotomy: a single-center experience sharing insights - Qingping Xia; Yong Cao; Jialuan Li; Jie Jiang; Xuan Lu; Li Deng (Frontiers in Cardiovascular Medicine)
ObjectiveThe objective of this study was to improve long-term postoperative survival in a porcine cardiac valve surgery model by utilizing cardiopulmonary bypass (CPB) via left thoracotomy. The study aimed to share refined techniques and insights accumulated over years at a single-center animal clinical trial facility.MethodA total of 196 Chinese Large White pigs weighing between 60 and 75 kg were used in the study. All animals underwent cardiac valve surgeries via left thoracotomy with CPB. Surgical techniques included mitral valve replacement, mitral valve repair, aortic valve replacement, OZAKI procedure, ascending aorta replacement, and left ventricular assist device implantation. Anesthesia and CPB protocols were optimized to minimize stress and complications. Postoperative care was standardized to enhance recovery and survival.ResultAll 196 pigs survived the surgical procedures, with no deaths reported. The mean surgical duration was 168.55 ± 38.75 min, CPB time was 114.89 ± 32.11 min, and aortic cross-clamp time was 76.75 ± 21.33 min. Automatic heart resumption occurred in 63.8% of pigs, while the remainder required electrical defibrillation or cardiac massage. The postoperative mechanical ventilation time was 2.44 ± 0.58 min, and the average drainage volume at 2 h postoperatively was 27.50 ± 9.70 ml. There were no cases of postoperative hemorrhage complications or blood transfusions, and surgical site infections occurred in only 1.5% of pigs.ConclusionThe surgical approach utilizing left thoracotomy with CPB has proven effective in significantly enhancing long-term survival rates in porcine heart surgeries. The refined techniques and standardized operational procedures described in this study offer valuable insights for researchers aiming to improve the success of porcine heart valve surgical models. However, due to differences in animal anatomy, the applicability of this surgical approach to other animal models still requires further exploration.